The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.5194/acp-2019-1174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidecadal trend analysis of aerosol radiative properties at a global scale

Abstract: <p><strong>Abstract.</strong> In order to assess the global evolution of aerosol parameters affecting climate change, a long-term trend analyses of aerosol optical properties were performed on time series from 52 stations situated across five continents. The time series of measured scattering, backscattering and absorption coefficients as well as the derived single scattering albedo, backscattering fraction, scattering and absorption Ångström … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Long term surface concentrations of BC in the Arctic have mostly decreased during the 1990s and 2000s (Hirdman, Burkhart, et al., 2010; Sharma et al., 2013). Recently, this trend seems to have leveled off with little to no trend observed for surface level BC in the Arctic during the last decade based on a trend analysis including all seasons (Coen et al., 2020). However, higher up in the Arctic atmosphere the situation might be different as East Asia is expected to contribute more substantially to the BC levels at higher altitudes (Ikeda et al., 2017; Sharma et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Long term surface concentrations of BC in the Arctic have mostly decreased during the 1990s and 2000s (Hirdman, Burkhart, et al., 2010; Sharma et al., 2013). Recently, this trend seems to have leveled off with little to no trend observed for surface level BC in the Arctic during the last decade based on a trend analysis including all seasons (Coen et al., 2020). However, higher up in the Arctic atmosphere the situation might be different as East Asia is expected to contribute more substantially to the BC levels at higher altitudes (Ikeda et al., 2017; Sharma et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all datasets are available as level 2 NASA/AMES files at EBAS (http://ebas.nilu.no/, last access: 20 July 2020) at an hourly resolution. The screened datasets used for this study aggregated as daily medians can be found at https://doi.org/10.21336/c4dy-yw57 (Collaud Coen et al, 2020b).…”
mentioning
confidence: 99%
“…For long term trends in BC, global emissions were estimated to grow by about 15% by 2010 compared to 1990 [50]. The aerosol light absorption levels do not show a significant trend in the Arctic as recently displayed in the analysis by Collaud Coen et al [22] for long term data from Arctic stations Alert, Summit and Zeppelin-Ny Ålesund.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, a study has found 10 year long trends to exhibit no statistically significant change for several areas including Svalbard (Ny-Ålesund), Greenland (Summit) and a slight increasing trend at Alert [22]. Despite global BC may have increased from 1990 to 2010, Arctic BC decreased dramatically over that same time span [19,23,24].…”
Section: Introductionmentioning
confidence: 99%